Troglomorphic adaptations on the northern European frontier: the phylogeny of the cave Pseudosinella (Hexapoda, Collembola) in the Western Carpathians - Kováč, Ĺubomír; Žurovcová, Martina; Raschmanová, Natália; Jureková, Nikola; Papáč, Vladimír; Parimuchová, Andrea (Frontiers in Ecology and Evolution, 2023)
The collembolan genus Pseudosinella Schäffer, 1897 (fam. Entomobryidae) includes more than 370 species with a predominantly Holarctic distribution, of which about 39% are restricted to caves. Using an integrative taxonomic approach, we investigated the morphological and molecular characters to identify the species of the genus Pseudosinella occurring in caves of the Western Carpathians, Central Europe, and to clarify their phylogenetic relationships. Based on morphological characters, we hypothesised that Pseudosinella aggtelekiensis (Stach, 1929) and P. paclti Rusek, 1961 originated from different phyletic lineages, the former species being recently morphologically distinct from its related edaphic counterparts. On the other hand, several congeners similar to P. paclti have been found in caves, superficial subterranean habitats, and soil. We used the barcoding fragment of the mtDNA cytochrome c oxidase subunit 1 (COI) gene from 87 individuals to reconstruct the phylogenetic history of the genus Pseudosinella from 16 caves in the Western Carpathians. The molecular phylogenetic tree revealed two distinct species groups with allopatric distributions. The first group consisted of P. aggtelekiensis populations from Slovak Karst and three undescribed species from fragmented and isolated karst areas in southeastern Slovakia. The second group, P. paclti populations in the Central Western Carpathians, was merged. This group also included P. muranensis, a new species taxonomically described in this work. It is characterised by highly developed troglomorphic features and is restricted to a small karst area, the Muránska planina Plateau. The phylogeny of the genus Pseudosinella from the caves of the Western Carpathians revealed a Miocene diversification. According to an approximate estimate of the geological time of species isolation, the two distinct lineages of Pseudosinella separated in the middle Miocene, about 14.51 Mya, followed by further diversification in the P. paclti lineage 10.89 Mya and in the P. aggtelekiensis lineage 11.14 Mya. This phylogeny is consistent with the uplift of Triassic limestones during the early formation of the Western Carpathians in the Paratethys region and the initial development of caves during this period. The study provides further important evidence that the Western Carpathians played a significant role as an independent speciation centre of the obligate cave fauna in Europe.